A Systematic Review of Thermosensation and Thermoregulation in Anxiety Disorders - Fischer, Susanne; Haas, Florence; Strahler, Jana (Frontiers in Physiology, 2021)
Objectives Sweating, hot flushes, and blushing are symptoms frequently reported by individuals with anxiety disorders. They represent important reinforcers of anxiogenic cognitions and behaviours. One system that may be involved in the manifestation of these symptoms is the thermosensory/thermoregulatory system. The aim of the present study was to investigate to what extent individuals with anxiety disorders are characterised by alterations in this system. Methods PubMed and PsycINFO were systematically searched. Studies were eligible if they i) assessed individuals with anxiety disorders, ii) thermosensation or thermoregulatory effectors/outcomes, and iii) used a case-control design. Results N=86 studies were identified. There was no evidence of altered thermosensation in individuals with anxiety disorders. Regarding thermoregulatory effectors, individuals with social anxiety disorder exhibited altered cutaneous vasodilation upon pharmacological challenge; individuals with specific phobia showed increased sweating upon confrontation with phobic stimuli; individuals with panic disorder showed increased daily sweating as well as increased sweating in response to non-phobic and phobic stimuli. Regarding thermoregulatory outcomes, there was evidence for altered skin temperature in all subtypes of anxiety. Conclusions Whereas there was no evidence of altered thermoregulation in specific phobia, a subgroup of individuals with social anxiety and panic disorder appears to exhibit altered vasodilation and sweating, respectively. Longitudinal research is warranted to investigate whether this represents a vulnerability to anxiety/panic.